2019
DOI: 10.1002/cbic.201900624
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Alcohol Dehydrogenase Catalysis in Deep Eutectic Solvent/Water Mixtures

Abstract: The use of oxidoreductases (EC1) in non‐conventional reaction media has been increasingly explored. In particular, deep eutectic solvents (DESs) have emerged as a novel class of solvents. Herein, an in‐depth study of bioreduction with an alcohol dehydrogenase (ADH) in the DES glyceline is presented. The activity and stability of ADH in mixtures of glyceline/water with varying water contents were measured. Furthermore, the thermodynamic water activity and viscosity of mixtures of glyceline/water have been deter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(75 citation statements)
references
References 77 publications
3
72
0
Order By: Relevance
“…To use nonaqueous media, that is, solvent‐free systems or organic solvents for redox catalysis, cofactor regeneration is still a challenge to be solved. During the 1980s and 1990s, extensive studies on the use of oxidoreductases under water‐deficient conditions were reported by the research groups of Klibanov and Adlercreutz, It has been shown that substrate‐coupled cofactor regeneration is possible in low‐water media, whereas enzyme‐coupled cofactor regeneration is still not trivial because the nicotinamide cofactor (oxidized and reduced forms) needs to diffuse from one active site to the second one during the course of the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…To use nonaqueous media, that is, solvent‐free systems or organic solvents for redox catalysis, cofactor regeneration is still a challenge to be solved. During the 1980s and 1990s, extensive studies on the use of oxidoreductases under water‐deficient conditions were reported by the research groups of Klibanov and Adlercreutz, It has been shown that substrate‐coupled cofactor regeneration is possible in low‐water media, whereas enzyme‐coupled cofactor regeneration is still not trivial because the nicotinamide cofactor (oxidized and reduced forms) needs to diffuse from one active site to the second one during the course of the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome these issues, the subfield of enzyme catalysis in organic solvents was constituted early and eventually. [238][239][240][241][242] It was 1980s-90s when the use of enzymes in non-aqueous media was documented by pioneers of the field: Klibanov, 243 Halling, 244 Mattiasson and Adlercreutz. 245 Furthermore, it was at the beginning of the 2000s, when the first papers were published on biocatalytic reactions in ionic liquids (ILs) (see also above, chapter 4.2.2).…”
Section: Non-conventional Mediamentioning
confidence: 99%
“…248 The topic of 'biocatalysis in non-conventional media' (BNCM) was recently augmented by the field of using deep eutectic solvents (DES) as efficient solvents and reaction (co) media in biocatalysis. 240,[249][250][251][252][253][254] DESs gained much attention in the last years being neoteric solvents which special benefits, such as an easy and fast preparation procedure and several tunable properties. Eutectic mixtures are obtained mixing Lewis or Brønsted acids and bases containing a variety of anionic and/or cationic species.…”
Section: Non-conventional Mediamentioning
confidence: 99%
See 2 more Smart Citations